Artificial Intelligence in Arabic Language Learning: Exploring Students’ Usage Patterns, Purposes, Benefits, and Perceptions - Akmal; Abdurrahman Wahid Abdullah; Ulyatul Khairat; Sitti Aminah; Irfan (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2026)
This study examines how students in Arabic Language Education program uses Artificial Intelligence (AI) to support Arabic language learning. Specifically, it explores students’ AI usage patterns, learning purposes, perceived benefits, and overall perceptions of AI-assisted Arabic language learning. This study employed a descriptive quantitative approach involving 89 students from several universities in Indonesia. Data were collected through an online questionnaire using a Likert-scale instrument and analyzed using descriptive statistics, including percentages and mean scores. The findings reveal that students reported a moderate level of AI use in Arabic language learning (M = 3.20), particularly for information searching (M = 3.53), text translation (M = 3.43), and vocabulary comprehension (M = 3.44). Students also perceived AI as useful, practical, and easy to use in supporting learning activities. Furthermore, AI was considered beneficial in improving learning efficiency, facilitating independent learning, and helping students understand difficult materials. However, students expressed concerns regarding the accuracy of AI-generated information and the potential risk of overdependence on technology. The findings indicate that AI has become an important supporting tool in Arabic language learning, although its use still requires critical awareness and academic supervision. While previous studies have mainly focused on AI effectiveness, technology acceptance, or specific applications in language learning, this study provides a comprehensive examination of students’ AI usage patterns, learning purposes, perceived benefits, and perceptions within Arabic language education. The findings contribute to the growing body of literature on AI-assisted language learning and offer practical insights for educators and institutions seeking to integrate AI responsibly into Arabic language instruction.